2014
DOI: 10.22226/2410-3535-2014-4-249-252
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of ultrafast heating on the structure and shape of the gas phase synthesized Cu nanoparticless

Abstract: Molecular dynamics method using the tight-binding potential to carry out simulation of ultrafast heating of the synthesized particles from the gas phase to a temperature T = 600 K and T = 900 K, at which the particles were kept about 10 ns. As a result of the simulation revealed that the method of ultrafast heating the particles to high temperatures virtually eliminates the possibility of a clusters of defective education, but as a result of the heat treatment, the some of investigated particles can disconnect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Under certain thermodynamic conditions, a coherent cluster structure is formed (all atoms both in the bulk and on the surface are considered). The results are in good agreement with the data of computer investigations of the condensation of nickel nanoparticles, 15,80 which demonstrated that coalescence plays an important role at early stages of the synthesis, that is, when the temperature in the system is high. In the case of intense cooling with an inert gas, the temperature rapidly decreases, and agglomeration giving multifractal diplo structures (see above) becomes the predominant growth mechanism.…”
Section: Simulation Of the Structure Of Transition Metal Nanoclusupporting
confidence: 87%
See 4 more Smart Citations
“…Under certain thermodynamic conditions, a coherent cluster structure is formed (all atoms both in the bulk and on the surface are considered). The results are in good agreement with the data of computer investigations of the condensation of nickel nanoparticles, 15,80 which demonstrated that coalescence plays an important role at early stages of the synthesis, that is, when the temperature in the system is high. In the case of intense cooling with an inert gas, the temperature rapidly decreases, and agglomeration giving multifractal diplo structures (see above) becomes the predominant growth mechanism.…”
Section: Simulation Of the Structure Of Transition Metal Nanoclusupporting
confidence: 87%
“…5, the cluster formation (bottomup along the time scale) 13,74,79,80 in the metastable gas phase started with homogeneous nucleation. 13,62,64 After completion of this process, different mechanisms of the subsequent growth are possible, the most important of these being agglomeration and coalescence.…”
Section: Simulation Of the Structure Of Transition Metal Nanoclumentioning
confidence: 99%
See 3 more Smart Citations